Breaking through the epistemic impasse: Ending homelessness with the invention of 'functional zero' in the Anglo-American world. (May 2021) - Evans, Joshua; Baker, Tom
Highlights: Critically reflects on the shifting terrain of homelessness governance in these 'liberal' welfare regimes. Traces how 'ending homelessness' has been conceptually reorganized through the concept of 'functional zero' and the epistemic temporalities that have been mobilized in the process. Reveals a fundamental tension between future-orientated, long-term perspectives and present-focused governance imperatives in the field of homelessness policy. Suggests concepts, such as functional zero, particularly rich for understanding the shifting political terrain of homelessness governance. Abstract: In this article, we examine strategies to 'end' homelessness in Anglo-American countries such as the United States, Canada and Australia. In the process, we critically reflect on the shifting terrain of homelessness governance in these 'liberal' welfare regimes. Beginning in the early 2000s, municipalities across the United States, and later Canada, reconfigured their homelessness policies around the ambitious goal of ending homelessness in 10 years. Grounded in evidence-based interventions such as Housing First, 10-year plans target resources toward the hardest-to-house, endeavor to achieve zero homelessness within a set time frame, and do so while purportedly reducing the economic cost of homelessness. In the time since these plans were initiated, ending homelessness, in an absolute sense, has proven elusive. These circumstances reveal an impasse: we have never known more about homelessness yet, in cities and nations of the Anglo-American world, we seem incapable of ending it. In the face of this impasse, an epistemological inquiry into the very meaning of 'zero' homelessness has emerged among homelessness experts and practitioners, one that focuses, in particular, on the notion of 'functional zero' and a new campaign called Built-for-Zero. We critically examine this discursive configuration and in doing so work to unpack its significance for homeless governance.